Glyphosate treatments for managing successional dynamics in beech bark disease-affected northern hardwood forests - Givelas, Mark; Gorgolewski, Adam; Duckett, Cameron; Martin, Adam R. (PloS one, 2025)
The spread of beech bark disease (BBD) in northern tolerant hardwood forests poses a significant forest management challenge. Extensive aboveground mortality in BBD-affected stands often leads to the rapid formation of high-density American beech ( Fagus grandifolia Ehrh.) thickets, primarily driven by vegetative regeneration through root sprouting. These thickets can outcompete desirable species such as sugar maple ( Acer saccharum L.), and negatively impact long-term forest structure and functions. This study evaluated the efficacy of post-harvest herbicide treatments—specifically the application of glyphosate to recently cut stumps and the use of “hack-and-squirt” application techniques on standing beech—to suppress vegetative beech regeneration. Over five years, beech regeneration was significantly lower in treatment plots, averaging 904 stems ha ⁻ ¹ (95% CI: 433−1,378 stems ha ⁻ ¹), compared to 1,741 stems ha-¹ (95% CI: 1,286–2,193 stems ha ⁻ ¹) in untreated control plots. Additionally, by five years post-harvest, glyphosate-treated plots supported higher densities of desirable tree species such as sugar maple, indicating that the intervention shifted species composition by reducing beech dominance. However this method had no significant effect on overall tree species richness or diversity, so while these treatments effectively suppress beech regeneration and promote successional trajectories in hardwood forests, they do not reduce tree diversity. By alleviating the competitive dominance of beech thickets, this management strategy is likely to mitigate the ecological and economic impacts associated with BBD, while maintaining or enhancing desirable tree species diversity.